Migrant Intimacies: Mobilities-in-Difference and Basue Tactics in Queer Asian Diasporas - Kojima, Dai (Anthropologica, 2014)
With a focus on the productive tensions of displace ments and agency, this article discusses archival traces of inti macy and tactics of space-making that mobilize queer Asian men in the diaspora. The theoretical considerations and ethno graphic examples offered highlight how ephemeral experiences of sociality and belonging reveal the persistent labour of recon stituting the lifeworlds of queer Asian migrant subjects against displacements—from city streets, to a video website, to a com muter train, to a night market—and argues for a rethinking of the meaning of politics in mobilities research through the modalities of survival and mobilities-in-difference.